Hassan, Jamal (London, 2006)
2006 "Hassan, Jamal", 2006, Bishopsgate Institute Jamal Hassan works at Camden Community Law Centre. He was a community and youth worker in the East End from 1972 until 1981. He was also involved with the Bangladesh Welfare Association (BWA). He became secretary of the coalition organisation which staged the demonstration from Brick Lane to Hyde Park. His transcript describes a number of turning points, the murder of Altab Ali in 1978, which focused nationwide attention on racism, and Len Murray's visit to Brick Lane that year (TUC General Secretary)